2023
DOI: 10.3390/foods13010144
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Volatile and Nonvolatile Metabolites in Black Tea under Four Second-Drying Methods Using Widely Targeted Metabolomics

Tianmeng Lan,
Qingbin Zeng,
Lin Chen
et al.

Abstract: Second-drying has an impact on the development of flavor and aroma in black tea. However, the effect of the shape changes of the tea leaves during second-drying on the quality of black tea has yet to be evaluated. In this study, GC-TOFMS and UPLC-HRMS identified 411 volatile metabolites and 253 nonvolatile metabolites. Additionally, 107 nonvolatile compounds and 21 different volatiles were screened. Significant alterations (p < 0.01) were found in 18 amino acid derivatives, 17 carbohydrates, 20 catechins, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Zhang C et al (2023) found that aged black tea showed a decreasing trend in the pH value in the liquid of tea along with the extension of the year, which might be related to the formation and accumulation of organic acids, such as L-ascorbic acid and salicylic acid [17]. The flavour performance of sweet aroma compounds in black tea may be due to the reduction in carbohydrates and acetylation of AAs during the period of hot-air second-drying [18]. Meanwhile, 620 differential substances were detected through metabolomics techniques during the manufacturing process of "Huangjinya" black tea [19].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang C et al (2023) found that aged black tea showed a decreasing trend in the pH value in the liquid of tea along with the extension of the year, which might be related to the formation and accumulation of organic acids, such as L-ascorbic acid and salicylic acid [17]. The flavour performance of sweet aroma compounds in black tea may be due to the reduction in carbohydrates and acetylation of AAs during the period of hot-air second-drying [18]. Meanwhile, 620 differential substances were detected through metabolomics techniques during the manufacturing process of "Huangjinya" black tea [19].…”
Section: Introductionmentioning
confidence: 99%